Biotechnologies demand caution, observes FAO again - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The same FAO Committee acknowledged the value of biotechnologies in plant tissue culture, improved genetic selection, conservation of threatened species, and cultivation of marginal lands. However, the committee stressed that agricultural problems...